Telephone‐based behavioral activation with mental imagery for depression: A pilot randomized clinical trial in isolated older adults during the Covid‐19 pandemic. (10th November 2021) - Pellas, Johnny; Renner, Fritz; Ji, Julie L.; Damberg, Mattias
Abstract: Objectives: To shield vulnerable persons, particularly the elderly, during the Covid‐19 pandemic governments around the world have advised to use social distancing and self‐isolation. Social isolation might put older adults at an increased risk for mental health problems such as depression. There is a need for brief, easy‐accessible psychological treatments for depressive symptoms that can be delivered remotely. The aim of this study was to investigate the feasibility, acceptability, and preliminary efficacy of telephone‐delivered Behavioral Activation with Mental Imagery (BA‐MI) for the treatment of depressive symptoms in individuals 65 years and older living in isolation during the Covid‐19 pandemic. Methods: In this open‐label pilot randomized clinical trial, N = 41 individuals aged 65 years or older with clinically significant symptoms of depression were randomly assigned to either a BA‐MI treatment condition, or an Attention‐Assessment control condition delivered over the telephone over a 4‐week period. Results: Depressive symptoms decreased more in the treatment condition compared to the control condition. At post‐treatment, 2 out of 16 participants in the treatment condition met diagnostic criteria for depression compared to 9 out of 13 in the control condition. Most participants in the treatment condition were satisfied with the treatment and few adverse effects were observed. Conclusions: This pilot study suggests that behavioral activation with mental imagery delivered over the telephone is feasible, acceptable, and potentially efficacious for the treatment of depressive symptoms in older individuals living in isolation. Replication in larger samples is needed. Key points: The Covid‐19 pandemic has exacerbated the need for brief, accessible psychological treatments for depressive symptoms that can be remotely delivered to isolated older adults. This pilot RCT investigated the feasibility and preliminary efficacy of telephone‐based Behavioral Activation with Mental Imagery (BA‐MI) for depression in this sample. BA‐MI led to a greater decrease in depressive symptoms and increases in behavioral activation in the treatment group compared to the control group. BA‐MI may help to alleviate depressive symptoms in isolated older adults.